A Blast-Resistant Method Based on Wave Converters with Spring Oscillator for Underground Structures. (10th May 2017) - Zhang, Yu; Liu, Yuanxue; Wu, Runze; Zhao, Jichang; Hu, Ming; Tan, Yizhong
Abstract : Researches on blast-resistant measures for underground structures such as tunnels and underground shopping malls are of great importance for their significant role in economic and social development. In this paper, a new blast-resistant method based on wave converters with spring oscillator for underground structures was put forward, so as to convert the shock wave with high frequency and high peak pressure to the periodic stress wave with low frequency and low peak pressure. The conception and calculation process of this new method were introduced. The mechanical characteristics and motion evolution law of wave converters were deduced theoretically. Based on the theoretical deduction results and finite difference software F L A C 3 D, the dynamic responses of the new blast-resistant structure and the traditional one were both calculated. Results showed that, after the deployment of wave converters, the peak absolute values of the bending moment, shear force, and axial force of the structure decreased generally, which verified the good blast-resistant effect of the new blast-resistant method.